Genetic Diversity in Hypervariable Segment I of Mitochondrial DNA Among the Kurdish Population Erbil City- Iraqi Kurdistan Region - Srwa yousif Anwer; Shakhawan Anwar Ali; Hazha Jamal Hidayat (Zanco Journal of Pure and Applied Sciences, 2026)
Analysis of human sequence polymorphisms of mitochondrial DNA (mtDNA) hypervariable segment 1 (HV1) has become a significant technique in forensic casework and is used for genetic diversity and human evolution evaluation, consanguinity identification, and mitochondrial illness diagnosis. The present study aimed to provide insights into the demographic history and origins of the Kurdish people in the Iraqi Kurdistan region by analyzing mitochondrial DNA (mtDNA) sequence variations, particularly focusing on hypervariable segment 1 (HVS I). The HVS I of mtDNA was sequenced in 120 unrelated individuals from the Kurdish population by using Sangar sequencing. The study's findings reveal significant genetic diversity among the Kurdish population's HVS I of human mitochondrial DNA (mtDNA). The sequence of HVS I within the non-coding region had 413 mutations across 402 sites, resulting in 111 different haplotypes, as compared to the revised Cambridge Reference Sequence (rCRS) to gauge genetic diversity and community variety. Comparing this population sample to rCRS, the mutations found were (17.055%) transition and (0.921%) transversion. The phylogenetic tree for the Kurdistan region revealed a considerable degree of community variety. In order to determine the Kurdish ancestry and demographic history in the territory of Iraqi Kurdistan, the results also showed that the mtDNA haplotypes were classified into mtDNA haplogroups. The most frequent haplogroups were U, H, J, and HV, with frequencies of 22.5%, 19.2%, 14.5%, and 12.9%, respectively; nevertheless, T and N had a moderate prevalence of 8% and 6.4%, respectively. The haplotype results exhibited that Europe and India had the most genetic diversity in common with the Kurdish people of Iraqi Kurdistan. The findings will contribute to a better knowledge of Kurdish mitochondrial genome diversity, as well as to demographic history and forensic science.